La utilización de la plataforma E-Commerce para la optimización de las Operaciones Comerciales en el Comisariato Súper Todo del Cantón Baba. - Engracia Lluccha, María Guadalupe (2015)
This research work of a very common problem at supermarkets, this problem has to do with the commercial management of the same, regardless of company size, this is mostly stay competitive and maintain a level of sales that ensure payback and logically a profit within allowable ranges. The project "Super Todo" this relevant to the difficulties mentioned in the previous paragraph, these difficulties has been corroborated by customers and by employees and the manager confirms everything mentioned in the problem description. The proposal proposed solution consists in implementing a Web portal with features Client / Server, which has been developed to automate the promotion and marketing of the products it sells the supermarket The web portal will allow each user can even be accessed from any computer with internet for business transactions, whether these sales, purchasing, product query or update data The tools that have been used for carrying out the website are the so- called free use, as follows: Apache, Mysql, Php and java script, an advanced platform also use wordpress 4.1. The portal will also allow the promotion of the company and its products permanently, 7 days a week, 24 hours a day, will also enable the expansion of markets both regionally and nationally It is expected that the effect described above the elevation of sales and thus improving the commercial management of the...